Forty years in the struggle the memoirs of a Jewish anarchist - Weinberg, Chaim Leib, 1861-1939.; Helms, Robert P.; ebrary, Inc. (Duluth, Minn. : Litwin Books, 2008)
"Memoir of Chaim Leib Weinberg, prominent member of the late 19th and early 20th century Philadelphia Jewish anarchist community, translated from the original Yiddish"--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Weinberg, Chaim Leib, -- 1861-1939.; Anarchism -- United States -- History; Jewish labor unions -- United States -- History; Jewish anarchists -- United States -- History -- 19th century; Jewish anarchists -- United States -- History -- 20th century; Jewish anarchists -- United States -- Biography; Electronic books